IMPROVING STUDENTS’ GENERIC SKILL IN SCIENCE THROUGH CHEMISTRY LEARNING USING ICT-BASED MEDIA ON REACTION RATE AND OSMOTIC PRESSURE MATERIAL (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The research aims to obtain information of improvement students’ generic skills in science through chemistry learning using ICT-based media on reaction rate and osmotic pressure material. This research was designed with quasi-experimental research method, with the design of non-equivalent control group pretest-posttest design. The research subjects were students of class XI and XII one of Madrasah Aliyah Negeri (State Islamic Senior High School) in Bandung. Learning process in experiment group were conducted using ICT-based media, whereas in control group conducted by applying laboratory activities. Data were collected through multiple-choice test. The result shows that there was no significant difference of n- gain of students’ generic skill in science between experiment and control group. Therefore it can be concluded that the learning process using ICT-based media can improve students' generic skills in science as well as laboratory-based activities.